2013
DOI: 10.4269/ajtmh.13-0148
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Bacteremic Melioidosis in Eastern and Northeastern, Thailand

Abstract: Melioidosis is among the most common causes of septicemia in Thailand, but data on economic burden are limited. We describe the economic impact of bacteremic melioidosis hospitalizations in two Thailand provinces during 2006–2008. Costs are presented in US dollars ($1 = 30.49 Thai Baht). The average annual incidence of bacteremic melioidosis cases per 100,000 persons in Sa Kaeo and Nakhon Phanom was 4.6 and 14.4, respectively. The annual cost of bacteremic melioidosis hospitalizations from the societal perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
(22 reference statements)
1
17
0
Order By: Relevance
“…54 The annual incidence of bacteremic melioidosis was reported to be 4.6 and 14.4 cases per 100,000 persons in two Thailand provinces. 122 A study on the etiology of severe CAP in Singapore between 1989 and 1993 revealed that B. pseudomallei was identified in 10 cases among 48 patients. 57 The presence of endemic melioidosis has been also reported from Northern Australia, [123][124][125][126] Cambodia, 127,128 Hong Kong, 129 India, 130 Taiwan, 131 and Southern China.…”
Section: Burkholderia Pseudomalleimentioning
confidence: 99%
“…54 The annual incidence of bacteremic melioidosis was reported to be 4.6 and 14.4 cases per 100,000 persons in two Thailand provinces. 122 A study on the etiology of severe CAP in Singapore between 1989 and 1993 revealed that B. pseudomallei was identified in 10 cases among 48 patients. 57 The presence of endemic melioidosis has been also reported from Northern Australia, [123][124][125][126] Cambodia, 127,128 Hong Kong, 129 India, 130 Taiwan, 131 and Southern China.…”
Section: Burkholderia Pseudomalleimentioning
confidence: 99%
“…Approximately 400 cases are diagnosed at Sunpasitthiprasong Hospital, Ubon Ratchathani, each year, of which about 150 result in death [ 7 , 20 ]. At Nakhon Panom Hospital, about 100 cases are diagnosed each year with about 30 deaths [ 21 , 22 ]. Melioidosis is one of the 83 diseases notifiable by law under the National Communicable Disease Surveillance system in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Following the high number of hospitalised patients and mortality rates due to this disease, expensive treatment and cost are needed, which may result in long-term economic effects on the society, including the loss of productivity. 8 …”
Section: Discussionmentioning
confidence: 99%
“… 7 As a solution, thorough treatment and management in the acute stage of this disease are essential, including a continuous eradication treatment. 8 Hospital costs and economic burden have become critical issues. 9 Based on the previous retrospective studies, 28 of melioidosis patients (32.9%) required an intensive care unit (ICU) admission at a teaching hospital in Kuala Lumpur from 1988 to 2010, 10 while 27 patients (20.3%) had to be admitted to the ICU at Singapore General Hospital from 1996 to 2002.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation